Alpine Skiing With total knee ArthroPlasty (ASWAP): impact on molecular and architectural features of musculo‐skeletal ageing. (August 2015) - Narici, M.; Conte, M.; Salvioli, S.; Franceschi, C.; Selby, A.; Dela, F.; Rieder, F.; Kösters, A.; Müller, E.
Abstract : This study investigated features of skeletal muscle ageing in elderly individuals having previously undergone unilateral total knee arthroplasty (TKA) and whether markers of sarcopenia could be mitigated by a 12‐week alpine skiing intervention. Novel biomarkers agrin, indicative of neuromuscular junction (NMJ) degeneration, tumor suppressor protein p53, associated with muscle atrophy, and a new ultrasound‐based muscle architecture biomarker were used to characterize sarcopenia. Participant details and study design are presented by Kösters et al. (2015). The results of this study show that NMJ degeneration is widespread among active septuagenarians previously subjected to TKA: all participants showed elevated agrin levels upon recruitment. At least 50% of individuals were identified as sarcopenic based on their muscle architecture, supporting the hypothesis that NMJ alterations precede sarcopenia. Notably, sarcopenia was strongly associated with the expression of p53, which seems to confirm its validity as a biomarker of muscle atrophy. Training did not significantly modify any of these biomarkers. In view of the lack of accretion of muscle mass in response to the alpine skiing intervention, we hypothesize that local muscle inflammation and oxidative stress may have blunted the anabolic response to training and promoted muscle breakdown in this elderly post‐TKA population.